Mice carrying an analogous heterozygous dynamin 2 K562E mutation that causes neuropathy in humans develop predominant characteristics of a primary myopathy. (4th March 2020) - Pereira, Jorge A; Gerber, Joanne; Ghidinelli, Monica; Gerber, Daniel; Tortola, Luigi; Ommer, Andrea; Bachofner, Sven; Santarella, Francesco; Tinelli, Elisa; Lin, Shuo; Rüegg, Markus A; Kopf, Manfred; et al.
Abstract: Some mutations affecting dynamin 2 ( DNM2 ) can cause dominantly inherited Charcot–Marie–Tooth (CMT) neuropathy. Here, we describe the analysis of mice carrying the DNM2 K562E mutation which has been associated with dominant-intermediate CMT type B (CMTDIB). Contrary to our expectations, heterozygous DNM2 K562E mutant mice did not develop definitive signs of an axonal or demyelinating neuropathy. Rather, we found a primary myopathy-like phenotype in these mice. A likely interpretation of these results is that the lack of a neuropathy in this mouse model has allowed the unmasking of a primary myopathy due to the DNM2 K562E mutation which might be overshadowed by the neuropathy in humans. Consequently, we hypothesize that a primary myopathy may also contribute to the disease mechanism in some CMTDIB patients. We propose that these findings should be considered in the evaluation of patients, the determination of the underlying disease processes and the development of tailored potential treatment strategies.